(untitled) (Advancements in Homeopathic Research, 2022)
Molluscum contagiosum is a common skin infection that is caused by a pox virus and occurs mainly in children. Molluscous growths have umbilicated appearance with cheesy material inside, spreading by direct contact and are found especially on face, neck, chest, limbs and genitals and it may attain a certain size and persist for an indefinite period. Homeopathy has an effective solution for a range of viral infections which includes molluscum contagiosum also. It is to be remembered that the medicines chosen will be based on the individual symptoms of the patient and not on the pathological entity of molluscum. One such documented case report of a 17 years male patient is illustrated in the following article, where Silicea 200 was prescribed on the constitutional framework after consideration of generalities and particulars. Improvement was documented by photographs and dermatology life quality index (DLQI) was also assessed during every follow-ups. Within 4 months all lesions of molluscum contagiosum on face and hand were annihilated.